2013
DOI: 10.1007/s10517-013-2321-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Proteasome Chymotrypsin-Like Activity during the Development of Human Mammary and Thyroid Carcinomas

Abstract: Changes in the proteasome chymotrypsin-like activity in mammary and thyroid carcinomas in comparison with the adjacent tissue were studied at stages T(1-4)N(0-3)M(0) and T(2-3)N(0-1)M(0), respectively. The activities changed in a wave-like manner over the course of mammary carcinoma growth in cases with and without metastases. The minimum increment of the activity in the tumor was recorded during the T(2)N(0) stage in the absence of local metastases. The increment of the activity reached the peak in N(1) tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 7 publications
0
7
0
2
Order By: Relevance
“…These modifications lead to a sharp increase in the chymotrypsin like proteasome activity. The mini mal difference from this activity in the conditionally normal adjacent tissue was shown to make up 150% (Shashova et al, 2013). The succession of changes in the proteasome pool of the thyroid papillary carci noma is shown in Fig.…”
Section: Proteasomes In the Thyroid Tumorsmentioning
confidence: 93%
See 1 more Smart Citation
“…These modifications lead to a sharp increase in the chymotrypsin like proteasome activity. The mini mal difference from this activity in the conditionally normal adjacent tissue was shown to make up 150% (Shashova et al, 2013). The succession of changes in the proteasome pool of the thyroid papillary carci noma is shown in Fig.…”
Section: Proteasomes In the Thyroid Tumorsmentioning
confidence: 93%
“…We studied in detail the characteristics of protea somes of different types of tumors of experimental ani mals and humans (Astakhova and Sharova, 2006;Astakhova et al, 2010;Zakharova et al, 2011;Spirina et al, 2012;Shashova et al, 2013). It was found that each type of tumor was characterized by a unique protea some pool.…”
Section: Proteasomes In the Thyroid Tumorsmentioning
confidence: 99%
“…A study of breast cancer tissue revealed the positive correlation between the expression of proteasome activator REGγ and ERα status [121]. On the whole, the development of estrogen-dependent malignant tumors is accompanied by an increase in the chymotrypsin-like activity of the proteasomes and a change in their subunit composition [122][123][124]. The use of proteasome inhibitors, together with antiestrogens, against the ER-positive culture of breast cancer leads to a significantly increased antitumor effect, compared to the action of these drugs in a single mode [125].…”
Section: Mutual Regulation Of Estrogen Receptors and Ubiquitin Proteamentioning
confidence: 99%
“…Proteasomes are involved in the pathogenesis of many cancers including breast, endometrial, and thyroid cancers [12,13]. We previously showed that the the ChTL and CL levels were higher in patients with HNSCC than in patients with chronic laryngeal hyperplasia associated with epithelial dysplasia.…”
Section: Introductionmentioning
confidence: 99%